Baduanjin exerts anti-diabetic and anti-depression effects by regulating the expression of mRNA, lncRNA, and circRNA - Tian An; Zhong-Chen He; Xin-Qing Zhang; Jun Li; Ai-Ling Chen; Fang Tan; Hong-Dong Chen; Bo-Han Lv; Juan Lian; Si-Hua Gao; Guang-Jian Jiang (BMC, 2019)
Abstract Background Baduanjin, a traditional Chinese exercise therapy, has been widely used in China to treat type 2 diabetes (T2DM) with depression (DD). However, the underlying mechanism of Baduanjin in anti-DD is unclear. This study was focused on investigating the effects of Baduanjin on symptoms of depression and blood glucose in patients with DD and the underlying mechanism. Methods We performed a 12-week Baduanjin intervention on patients with DD and longitudinally compared the differential expressions of lncRNAs, circRNAs, and mRNAs between pre- (BDD) and post- (ADD) Baduanjin intervention in the same group. Subsequently, Gene Ontology (GO) and pathway analysis was performed to investigate the function of differentially expressed mRNAs. Finally, Reverse Transcription-Polymerase Chain Reaction (RT-PCR) was used to verify the sequencing result and the mRNA-lncRNA regulatory network was constructed. Results The blood glucose level, depression index scores, and PHQ9 scores of the patients with DD were significantly decreased (P < 0.05) after Baduanjin intervention. Compared to BDD, 207 lncRNAs, 266 circRNAs, and 610 differentially expressed mRNAs were identified in ADD. Kyoto Encyclopedia of Genes and Genomes (KEGG) and GO showed that the significantly dysregulated mRNAs were mainly involved in immune function and inflammatory response pathways, and various signaling pathways including IL-17 and TNF. In addition, we selected five differentially expressed lncRNAs to construct an lncRNA-mRNA regulatory network, and found a total of 1045 mRNAs associated with them. Conclusions Our research is the first systematic profiling of mRNA, lncRNA, and circRNA in patients of ADD and BDD, and provides valuable insights in the potential mechanism of Baduanjin in anti-DD. Further, it was confirmed that Baduanjin is a safe and effective intervention for patients with DD because it can effectively ameliorate the symptoms of depression and blood glucose levels in patients with DD by regulating the dysregulated expression of lncRNA, mRNA, and circRNA.